1991
DOI: 10.1177/027836499101000601
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Simplified Hopping Robot

Abstract: The authors construct a simplified model of a dynamically dexterous robot, M.H. Raibert's hopper, and investigate its elegant, physically based control strategies. Analysis of induced discrete dynamics leads to strong conclusions concerning global limiting properties. These conclusions are then verified by computer simulation of the simplified models, the correspondence of which to the true physical apparatus is seen to be acceptable as well. Comments Copyright 1988 IEEE. Reprinted from Proceedings of the IEEE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
176
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(178 citation statements)
references
References 12 publications
1
176
0
1
Order By: Relevance
“…In further defense of our coarse abstraction we observe that these models are sufficiently complex that so far the only analytical results for work-directed controllers encompassing physical actuator models explicitly coupled to the physical body state model have been obtained for one degree of freedom bodies (e.g. such as [35]) and that we see the present analysis as a first step along the way to that more informative but far less tractable problem. We also observe that no smooth workdirected scheme has heretofore been shown to converge even on T 2 .…”
Section: B Motor Modelmentioning
confidence: 86%
“…In further defense of our coarse abstraction we observe that these models are sufficiently complex that so far the only analytical results for work-directed controllers encompassing physical actuator models explicitly coupled to the physical body state model have been obtained for one degree of freedom bodies (e.g. such as [35]) and that we see the present analysis as a first step along the way to that more informative but far less tractable problem. We also observe that no smooth workdirected scheme has heretofore been shown to converge even on T 2 .…”
Section: B Motor Modelmentioning
confidence: 86%
“…Earlier studies of vertically constrained hopping revealed that the combination of constant energy input with viscous damping in the leg yields global, asymptotic stability as a result of the associated unimodal return map. 18 Following a similar line of inquiry, we find it most convenient to work in a new set of coordinates, the apex height, and the total mechanical energy, yielding a new return map definition, a simple coordinate change away from the map described in Sec. II C as ͫ y a ͓k + 1͔ E a ͓k + 1͔ ͬ = P ͩͫ y a ͓k͔ E a ͓k͔ ͬͪ .…”
Section: A Equilibrium Points Of the Uncontrolled Return Mapmentioning
confidence: 99%
“…[13][14][15][16][17] This led to the development of the simple yet accurate SLIP model to describe such behaviors. 18,19 Significant research effort was devoted to both the use of this model as a basis for the design of fast and efficient legged robots 1,2,20,21 and associated control strategies 22,23 as well as its analysis to reveal fundamental aspects of legged locomotory behaviors. 11 The present paper falls into the latter category and contributes by investigating the previously unaddressed question of how the presence of passive damping and actuation through a controllable hip torque affects the behavioral characteristics of running.…”
Section: Introductionmentioning
confidence: 99%
“…Though not indicated in the figure, massless springs may be attached between links and between links and the inertial reference frame; prismatic joints between links are also allowed. This class of systems clearly includes the Acrobot [2,36,52], the brachiating robots of [15,34,35,46], the gymnast robots of [32,39,57] when pivoting on a high bar, and the stance phase models of Raibert's onelegged hopper [1,6,14,26,33,42] as well as RABBIT [7][8][9][10]41]. The control objectives will be to stabilize the system about an equilibrium point or to track a set of reference trajectories with internal stability.…”
Section: Motivating Classes Of Systemsmentioning
confidence: 99%